Assessing The Implementation of Egypt’s Education 2.0 Reform: The Case of Sohag - Zahran, Norhan (AUC Knowledge Fountain, 2023)
Education is a key component contributing to a country’s socioeconomic status. Accordingly, countries that seek better economic development focus on the quality of education. Egypt realized that and started a series of educational reforms, none of which delivered the desired objectives. Regrettably, this was clear in Egyptian students' poor performance on international tests in the years 2013/2014 and 2014/2015 (World Economic Forum 2013; 2014). In 2018, the Egyptian Ministry of Education announced the launch of Education 2.0 (EDU 2.0) reform which adopted transformative, multidisciplinary, student-centered educational pedagogies to enhance the quality of education. This study presents the results of an evaluation of Education 2.0 reform’s influence on the quality of education in Sohag’s primary schools (grades 1-5), one of Upper Egypt’s governorates. Sohag ranks as the second poorest governorate in Egypt, with low government expenditure, which would impose more critical challenges during the implementation of EDU 2.0 innovative reform. The main research question is: To what extent was the implementation of Education 2.0 reform effective in Sohag? A qualitative methodology was utilized that depended on collecting data from three main stakeholder groups: Sohag public and private school teachers, educational advisors who were involved in the design and implementation of Education 2.0 reform, as well as parents in Sohag. A total of twenty-nine participants were involved through in-depth interviews and focus groups, and the interviewing stopped when no further insights were being derived from the interviews. The evaluation process managed to identify the main challenges as perceived by the Ministry of Education and Technical Education (MOETE) during the design and implementation of the reform, for instance, the resistance of parents and the robust parallel economy of private tutoring. Besides, the study recognized several difficulties faced by teachers and parents in Sohag during the execution phase, such as insufficient resources and inappropriate professional development training timings. Moreover, the analysis pointed out the reform’s perceived positive aspects alongside major concerns that might impact its effectiveness in Sohag. Generally, the teachers were satisfied with the innovative educational pedagogies and student- centered approaches and were delighted with the change in their students' performance. However, some of the identified major concerns were the teachers' insufficient support from the Ministry of Education and Technical Education (MOETE), the ineffective professional development training, and parents' dissatisfaction with EDU 2.0 reform; the latter factor threatening to be a possible cause for disruptive decisions by parents and their choice to withdraw their children from EDU 2.0 schools. Finally, the study came up with a number of recommendations based on past successful reforms executed in other international education reform experiences, and these were tailored to the Egyptian context, such as reinforcing teachers' communities of practice and enhancing parents' involvement through door-to-door campaigns.